The Trend of Social Collaboration as a Transformative Strategy for Environmental Degradation Mitigation in Coastal Villages - Amir, Muhammad; Batara, Suriyani Bunga; Liwaul; Ningtyas, Candra Puspita; Rijal, Muh. (CV. Literasi Indonesia, 2025)
This study aims to analyze social collaboration between the community and the government of Tanjung Tiram Village in mitigating environmental degradation, particularly through deliberative forums, collective actions, and educational programs. The research employed a descriptive qualitative method with observation, in-depth interviews, and documentation to explore lived experiences and real practices in the field. The findings reveal that collaboration manifests as a complementary partnership, with the community serving as the primary actor in actions and the government acting as the policy facilitator. Mitigation strategies encompass preventive measures through waste education, rehabilitative actions through reforestation, and adaptive responses via the use of organic fertilizers, emphasizing the importance of socio-ecological synergy. This study is significant as it demonstrates that coastal communities with limited resources are capable of developing a participatory-based mitigation model. Its practical implication lies in the potential replication of this model in other coastal villages, while also contributing to the literature on community-based governance. However, the study is limited to one location with a social focus; therefore, further research is recommended to integrate technical ecological aspects and conduct comparative analyses across different regions.